LEARNING RESULT DIFFERENCE MOODLE–BASED ANALYSED BY GROUP INVESTIGATION LEARNING MODEL IMPLEMENTATION AND CRITICAL THINKING ABILITY - Nashar Nashar; Ana Nurhasanah; Rikza Fauzan (Universitas Sultan Ageng Tirtayasa, 2020)
This research objective is to investigate the difference of learning result Moodle-based by group investigation learning model implementation and critical thinking ability. The type of this research is quantitative using treatment design by level 2x2. The data of this research was taken by observation result, test and questionnaire. The data analysis technique using two way annova test and t test to investigate the difference of learning result moodle-based after treatment. The result shows that (1)The learning result of moodle-based using group investigation learning model is better than using convntional learning model; (2)There is interaction between learning model and critical thinking ability toward learning result moodle-based; (3) The learning result moodle-based using group investigation learning model with high critical thinking ability is better than using conventional learning model with high critical thinking ability; (4) The learning result moodle-based using conventional learning model with low critical thinking ability is better than using group investigation learning model with low critical thinking ability. Theoritically, this research result can be used as a direction to improve the learning model and evaluation tool base on e-learning. Furthermore, hopefully there will be a research which use learning model and evaluation tool base on e-learning with another independent variable that effect the learning result. Keywords: group investigation, critical thinking ability and learning result moodle-based